Community case study for surveillance and early case-detection of SARS-CoV-2 infections across high-risk key populations: the Sentinella programme - Maela Tebon; Ruth Joanna Davis; Alessia Savoldi; Nicola Soriolo; Sarah Elizabeth Jane Walters; Michela Nosè; Corrado Barbui; Giulia Turrini; Elisa Danese; Giuseppe Lippi; Riccardo Cecchetto; Annarita Mazzariol; et al. (Frontiers Media S.A., 2024)
At the beginning of the COVID-19 pandemic, an ad hoc organisational framework was established between academic, local government and community partners to implement the "Sentinella - Identify, Trace and Prevent" screening programme in Verona, north-east Italy. Between September 2020 and May 2021, key populations not covered by any screening policies at the local and national level were screened for SARS-CoV-2. Target populations were: older adult residents (males >65 years and females >75 years), bus and taxi drivers, social workers, supermarket employees, hospital cleaning and catering staff, researchers working in the local hospitals, students, and people experiencing homelessness (PEH). Five dedicated swab clinics, home testing facilities, and one mobile clinic were activated to collect nasopharyngeal swabs. Molecular analysis was performed for all the subjects; an antigen-rapid diagnostic test (Ag-RDT) was also implemented as a point-of-care test for PEH. Medical follow-up, psychological support, and quarantine facilities were organised for subjects who tested positive for SARS-CoV-2. Overall, 2075 subjects participated in the surveillance programme. Amongst these, 1,572 were residents/workers, whilst 503 were PEH. A total of 127 (6.2%) participants tested positive for SARS-CoV-2. Sixty-nine were residents, 58 PEH. The incidence rate was 4 per 10.000 person/day (95% CI 3.1-5.0). The highest prevalence and incidence rates were found amongst supermarket employees (9.7% and 8.5 per 10.000 person/day, 95% CI 3.81-18.86, respectively), followed by hospital cleaning staff (8.1%, 7.6 per 10.000 person/day, CI 95% 4.9-11.7). Regarding PEH, the prevalence of SARS-CoV-2 was 11.5%. All PEH identified as positive were isolated in dedicated shelter facilities. Amongst the 69 residents/workers who were quarantined, 53 were reached for initial psychological support for assessing the presence of any psychological distress or psychiatric pathology. Amongst the subjects evaluated, 10 (18.9%) presented clinically significant psychological discomfort and accessed the stepped-care psychological intervention. The community partnerships played a pivotal role in optimising early case detection. Promotion of testing helped to prevent and contain more efficiently potential clusters through strategic planning, especially for PEH. Insights from the study highlight the importance of community partnerships in public health emergencies, particularly in the context of highly transmissible diseases pathways.